Research on algorithm for raster map multi-level sharing based on region incrementing color visual cryptography - Liguo FANG; Zhengxin FU; Hao HU; Gang SHEN; Bin YU (Tongxin xuebao)
In view of the characteristics of raster map,important data of the map were divided into different map layers by using the idea of map segmentation.A regional incremental color visual cryptographic scheme for raster map sharing was designed,and a model based on this scheme was proposed.At the same time,the specific application process was given.In order to solve the problem of large pixel expansibility and poor visual effect of image recovery in traditional regional incremental visual cryptography scheme,random numbers and the access structure optimization were used.Construction of the method was simple and the additional overhead of generating and saving the encryption matrix was avoided.The experimental results show that the scheme can achieve multilevel raster map sharing with the map’s perfect recovery,meanwhile the extension of the scheme pixel is greatly reduced.